Implications of an Aging Population on Government Expenditure in Malaysia - Amri Sulong; Mohd Kamal Mat Desa; Abdul Rashid, Noor Akma; Nik Zaid, Nik Nor Azila (Journal of Social Transformation and Regional Development, 2024)
This study investigates the implications of an aging population on government spending in Malaysia using the Fully Modified Ordinary Least Squares (FMOLS) method. Employing data spanning from 1992 to 2022, the study examines the relationship between the dependent variable, Government Expenditure, and the independent variable, Aging Population, while controlling for Gross Domestic Product and Unemployment as additional factors. The results reveal a positive connection between the aging population and government expenditure. As Malaysia experiences demographic shifts characterized by increased life expectancy and declining fertility rates, the findings suggest that addressing the needs of an aging population contributes to higher government spending. This study underscores the importance of recognizing and addressing the fiscal implications of demographic changes, providing valuable insights for policymakers in formulating strategies to navigate the challenges posed by an aging society in Malaysia.